2014
DOI: 10.1038/onc.2014.68
|View full text |Cite
|
Sign up to set email alerts
|

The TRIM-FLMN protein TRIM45 directly interacts with RACK1 and negatively regulates PKC-mediated signaling pathway

Abstract: The receptor for activated C-kinase (RACK1), a scaffolding protein that participates in the protein kinase C (PKC) signaling pathway, has an important role in shuttling active PKCs to its substrate. Indeed, recent studies have revealed that RACK1 has an important role in tumorigenesis and that enhancement of the feed-forward mechanism of the c-Jun N-terminal kinase (JNK)-Jun pathway via RACK1 is associated with constitutive activation of MEK (MAPK-ERK kinase)-ERK (extracellular signal-regulated kinase) signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…As PI3K-Akt and Ras-MAPK signaling pathway are the most frequently activated signaling pathways involved in gliomagenesis and TRIM45 was also reported to be associated with PKC-mediated modulation of the ERK-JNK and NF- κ B signaling pathway, 19, 20 we examined the phosphorylation status of AKT, ERK, JNK, p38, and IKK β in TRIM45-overexpressing or TRIM45 KO glioma cells. We did not detect any change in the phosphorylation status of all the kinases examined, regardless of whether the expression of TRIM45 was upregulated or downregulated (Supplementary Figures 7A and B), suggesting that TRIM45 does not affect the PI3K/AKT, MAPK, and NF- κ B signaling pathways in glioma cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As PI3K-Akt and Ras-MAPK signaling pathway are the most frequently activated signaling pathways involved in gliomagenesis and TRIM45 was also reported to be associated with PKC-mediated modulation of the ERK-JNK and NF- κ B signaling pathway, 19, 20 we examined the phosphorylation status of AKT, ERK, JNK, p38, and IKK β in TRIM45-overexpressing or TRIM45 KO glioma cells. We did not detect any change in the phosphorylation status of all the kinases examined, regardless of whether the expression of TRIM45 was upregulated or downregulated (Supplementary Figures 7A and B), suggesting that TRIM45 does not affect the PI3K/AKT, MAPK, and NF- κ B signaling pathways in glioma cells.…”
Section: Resultsmentioning
confidence: 99%
“…As TRIM45 is an E3 ligase, 19 we next determined whether TRIM45 affects p53 stability via ubiquitination. First, we found that TRIM45 promoted the polyubiquitination of p53 in a dose-dependent manner (Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 It has been shown that the PRYSPRY region of TRIM proteins is involved in molecular recognition and has antiviral activity. 17 Among the TRIM protein family, TRIM39 and TRIM45 have been reported to modulate inflammatory signaling through inhibition of the nuclear factor kB (NF-kB)-and protein kinase C-mediated pathways, 18,19 whereas TRIM40 is protective in inflammation-associated carcinogenesis in the gastrointestinal tract. 20 Moreover, TRIM22 variants are involved in early and adult-onset of IBDs through regulating the NOD2 signaling pathway.…”
mentioning
confidence: 99%
“…Cells stably overexpressing 3×Flag-RNF207 were established by a retroviral expression system using pMX-puro with puromycin (8 µg ml -1 , Sigma) selection as described previously [26].…”
Section: Cell Culturementioning
confidence: 99%